2019
DOI: 10.1109/access.2019.2905143
|View full text |Cite
|
Sign up to set email alerts
|

The Introduction of a Novel Virtual Reality Training System for Gynecology Learning and Its User Experience Research

Abstract: The researchers of this study designed a new virtual reality (VR)-assisted training system, IFOREAL, for gynecology students at their university and introduced it to potential trainees. Two versions of IFOREAL, each employing different devices, were developed. The consumer version uses a traditional LCD display and computer mouse, whereas the professional version utilizes a head-mounted display (HMD) and joystick controller for the virtual learning. Trainees watched simulated videos and interacted with the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
1
20
0
2
Order By: Relevance
“…The results for presence were on average 4.75/7 (SD = 1.07), which we consider reasonable. This is also confirmed by other recent VR studies yielding presence values in the same range (see Chang et al 2019;Zenner et al 2020). The average mental demand was 3.14/10 (SD = 2.01), which is rather on the lower end.…”
Section: Descriptive Resultssupporting
confidence: 89%
“…The results for presence were on average 4.75/7 (SD = 1.07), which we consider reasonable. This is also confirmed by other recent VR studies yielding presence values in the same range (see Chang et al 2019;Zenner et al 2020). The average mental demand was 3.14/10 (SD = 2.01), which is rather on the lower end.…”
Section: Descriptive Resultssupporting
confidence: 89%
“…An overview of these studies, their methodologies, and their findings are reported in Table 1 . Two of the included studies were published in 2016 (Allen et al, 2016 ; Robert et al, 2016 ), three in 2017 (Cárdenas-Delgado et al, 2017 ; Munafo et al, 2017 ; Wilson and Kinsela, 2017 ), eight in 2018 (An et al, 2018 ; Juan et al, 2018 ; Khashe et al, 2018 ; Melo et al, 2018 ; Mousas et al, 2018 ; Rangelova and Marsden, 2018 ; Roettl and Terlutter, 2018 ; Scheibler and Rodrigues, 2018 ), eight in 2019 (Al Zayer et al, 2019 ; Bracq et al, 2019 ; Chang et al, 2019 ; Clifton and Palmisano, 2019 ; Liang et al, 2019 ; Moroz et al, 2019 ; Narciso et al, 2019 ; Shafer et al, 2019 ), and one in 2020 (Curry et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Female participants achieved a higher level of spatial presence, realness, and overall presence when HMD was used to show 3D images (Narciso et al, 2019 ). According to one study, females were also more willing to adopt the use of HMD VR compared to males (Chang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Self-report questions measuring a user's perception and experience of using the current STEVRDS were utilized to collect subjective data. These gauged constructs have been used in the context of either VR or AR to better understand users' evaluations of systems (e.g., [22]- [28]). To ensure the quality of the measurements for these constructs, this study borrowed/revised the scales from the authors' prior study on a VR gynecological training system (i.e., [22]), which were developed from relevant AR/VR research, early classical studies, or studies that have been frequently cited in articles about information/computer systems and technologies.…”
Section: ) Subjective Measures Of User Perceptions Of the Systemmentioning
confidence: 99%